Psychotherapy and the highly sensitive person : improving outcomes for that minority of people who are the majority of clients - Aron, Elaine (Routledge, 2010)
In Psychotherapy and the Highly Sensitive Person, Dr. Elaine Aron redefines the term "highly sensitive". She dispels common misconceptions about the relationship between being sensitive and other personality traits, such as being introverted, and further defines the trait for the benefit of both the clinician and patient. Dr. Aron's book suggests ways to adapt treatment for highly sensitive patients and how to deal with the issues that usually arise, providing a helpful guide for both doctor and patient.